2017
DOI: 10.1111/ijfs.13555
|View full text |Cite
|
Sign up to set email alerts
|

Enzymolysis reaction kinetics and thermodynamics of rapeseed protein with sequential dual‐frequency ultrasound pretreatment

Abstract: SummaryWe evaluated the effect of sequential dual-frequency ultrasound (SDFU) pretreatments on rapeseed protein enzymolysis, using alcalase as a model enzyme. Hydrolysed protein concentrations, enzymolysis kinetics and thermodynamic parameters were investigated. The results showed that the hydrolysed rapeseed protein concentration following SDFU pretreatments was higher compared to that of the control for up to 75 min of enzymolysis at various substrate concentrations of 5-25 g L À1 ; both control and SDFU pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This indicated that ultrasound treatment had a negligible impact on the value of Δ G . Wali et al [42] used the sequential dual-frequency ultrasound pretreatment method to extract rapeseed protein and observed that Δ H , Δ S , and E a decreased by 31.78%, 18.0%, and 29.56 %, respectively. The change in the Δ G was insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that ultrasound treatment had a negligible impact on the value of Δ G . Wali et al [42] used the sequential dual-frequency ultrasound pretreatment method to extract rapeseed protein and observed that Δ H , Δ S , and E a decreased by 31.78%, 18.0%, and 29.56 %, respectively. The change in the Δ G was insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of VES is usually facilitated by the addition of succinic anhydride in excess of the stoichiometric ratio. However, it is imperative to carefully select an appropriate molar ratio of the substrate to strike a balance because an excessive amount of succinic anhydride not only escalates the overall cost, but also hampers the subsequent purification steps 45 . The esterification reaction was carried out in the range of different substrate molar ratios (1:1–1:7), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This higher efficiency of enzymolysis was attributed to the significant decrease in the kinetic and thermodynamic parameters K M and E a . [103] /2018 Rapeseed meal protein concentrate Fig. 1 C Frequency: 20, 28, 35, 40, and 50 kHz; Power density: 150–200 W/L.…”
Section: Application Of Power Ultrasound In Enzymolysis Of Proteinmentioning
confidence: 99%